Quantifying the Digital Divide: A Mixed-Method Analysis of Socio-Economic Determinants, Educational Employment Mismatch Index (EEMI), and Female Labor Force Participation in India (2017–2024) - Badlani, Meghna; Rami, Gaurang (JPAIR Multidisciplinary Research, 2025)
This study analyzes how digital access and educational attainment shape female labor force participation in India from 2017 to 2024. Using nationally representative unit-level data from the Periodic Labor Force Survey (PLFS) and National Family Health Survey (NFHS-5), it examines how digital inclusion and education jointly influence women’s access to formal and decent employment. The findings reveal that while digital connectivity improves women’s labor market entry, entrenched socio-cultural norms and regional disparities continue to restrict participation, particularly among rural and marginalized groups. To quantify this, disconnect, the study introduces the Educational–Employment Mismatch Index (EEMI), which captures the gap between women’s academic qualifications and their presence in the formal sector. EEMI is computed only for women with more than 12 years of education to ensure valid mismatch detection Results show that education alone does not ensure economic inclusion unless complemented by digital infrastructure, institutional support, and gender-responsive labor policies. The paper calls for integrated strategies that bridge these gaps and enable meaningful female workforce participation.